Varieties of the English Language in Nigeria: The Socio-Linguistic Implication on Communication. - Akujobi , O. S.; Umoh, G. I. (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
The debate over the existence and non-existence of a variety of English known as Nigerian English (N.E) has continued to be a subject of increasing research in Nigeria. Some scholars are completely opposed to the concept. This group, following the perspective of error analysis, holds the view that N.E is a deviation in the use of English from British norms. Others insist that N.E is among the developing varieties of world Englishes. This paper examines the different varieties of the Nigerian English and the sociolinguistic implications it has on communication. The study used questionnaires as instruments of data collection which were analysed using the Statistical package for the Social Sciences (SPSS) data analysis. The study shows that varieties of the English language in Nigeria create barriers in communication among categories of people in the societies. Finally, the paper recommends that the standard variety (variety III) should be standardized and institutionalized to aid effective communication. Also, Nigerian English should assume a status with features that will aid its national and international identity.